Public Relations of Public Libraries in Ankara - Karadeniz, Şenol (Information World, 2010)
In this study the answers to the question “why the public libraries in Ankara could not inform their users about services off ered properly, and could not introduce themselves to users suffi ciently ?” were explicated. The goal of the study is to fi nd out which public relations methods can be used in libraries, and why libraries could not conduct planned public relations activities. The research universe consists of public libraries being administratively connected to Ministry of Culture and Tourism, which lie within the borders of Ankara Metropolitan Municipality. For the collection of data, pre-confi gured talks were applied to the managers who were working for the public libraries, and moreover the fulfi llment of library activities were observed. The fi ndings of the study indicate that, since the public libraries could not apply systematic public relations programs, they become inadequate in introducing themselves and hence are not able to create a positive feedback on their users.
Keywords: Public libraries; Public relations; Marketing